Evolution of Microstructure and Microsegregation of Ti-45Al-8Nb Alloy during Directional Solidification - Xiangjun Xu; Rui Hu; Junpin Lin; Jian Guo (Advances in Materials Science and Engineering)
High Nb-containing TiAl alloys have good oxidation resistance and mechanical properties, but the microstructure and the properties are substantially affected by the segregation. To quantitatively investigate the segregation behavior of Al during solidification, microstructures of directionally solidified (DS) Ti-45Al-8Nb (in atomic percent) alloy prepared at withdrawing rates of 30 μm/s and 200 μm/s and a temperature gradient of 4200 K/m were observed by optical microscope and electronic probe microanalyzer. The microsegregations were characterized by wave dispersive spectroscopy. The results show that the DS ingots include the no melting zone, directionally solidified zone with columnar grains, mushy zone, and quenched liquid zone. The primary dendritic arm spacings are 353 μm and 144 μm, respectively, for the two ingots. But the solidified microstructures of the ingots are large lamellar colonies, which contain a few B2 patches and γ bands induced by microsegregation. From dendritic zone to columnar zone, the volume fractions of B2 patches and γ bands decrease. The segregation extents of Al and Nb decrease with the increase of solidification rate. There exists an obvious back diffusion process of Al during solidification and cooling after solidification. According to evolution of Al concentration profiles from mushy zone to columnar grain zone, interdiffusion coefficient for Al in β-Ti at near solidus temperature is semiquantitatively calculated, and the value is (6 – 11) × 10−11 m2/s.